Dictionary based English Speech to Marathi Speech Translation - Jadhav, Ruchita S. (Journal of Advanced Research in Information Technology, Systems and Management; Vol 3 No 2 (2019): Journal of Advanced Research in Information Technology, Systems & Management, 2021)
People of different language producing background could not able to interact with each other. This concept of translation will help people to communicate each other with well off. Also it will help to fill communication gap between two linguistically different backgrounds. It will help to the people who belongs from different villages, who have taken education of English. Majority of the Indian community is not recognized with English while most of the information available on web or electronic information is in English. Many Time government documents and forms are been presented in English Language where a lay man from Marathi language background finds difficulty to understand information and even avoid. Machine Translation able to translate Information presented in one language to other language with proper meaning. Information can be present in form of text, speech and image translating this information helps for sharing of information and ultimately information gain. The main objective of Machine Translation is to removed the language barrier in a bilingual nation like India. Machine Translation gives several approaches to translate source language to target language. In this project we are translating English to Marathi sentences for kids based on dictionary. How to cite this article: Jadhav RS, Tile MP, Shirude PN et al. Dictionary based English Speech to Marathi Speech Translation. J Adv Res Info Tech Sys Mgmt 2019; 3(2): 7-10